Hairy Cell Leukemia: Morphological and Immunophenotypic Characteristics of Seven Cases and Cyclin D1 Expression - Ramesh, Shruti Neelamegam; Padhi, Somanath; Adhya, Amit K.; Panigrahi, Ashutosh; Das, Prabodha K.; Patra, Susama (Indian Journal of Medical and Paediatric Oncology, 2021)
Aberrant immunophenotypic expression in hairy cell leukemia (HCL), both at medullary and extramedullary sites, is not uncommonly reported in literature. Cyclin D1 positivity in HCL may mimic mantle cell lymphoma (MCL) morphologically, especially in the presence of aberrant CD5 immunopositivity, requiring BRAFV600E mutation and/or CCND1 gene testing for confirmation. Here, we describe seven cases of HCL with clinicomorphological and immunophenotypic characteristics with an emphasis on cyclin D1 expression using immunohistochemistry (IHC) with a brief comprehensive literature review. We suggest that cyclin D1 positive HCL may be a distinct subtype which requires further immunophenotypic and molecular characterization for accurate diagnosis and planning of definitive therapy.
Keywords: hairy cell leukemia; trephine biopsy; translocation; therapy